Estimating building costs for the residential & light commercial construction professional - DelPico, Wayne J.; DelPico, Wayne J. (Hoboken, N.J. : RSMeans, 2012)
'Completely revised, updated, and reorganized to conform to Masterformat 2010, this new edition provides a step-by-step guide to estimating building costs for contractors. A series of questions at the end of each chapter helps the reader summarize the content. In addition, the chapter on computer estimating has been expanded to cover the new estimating software for performing quantity takeoff by computer, and content covering the procedures for conceptual estimating as well as parametric estimating has been added'--
'A step-by-step guide to estimating building costs for contractors, completely updated and reorganized to conform to Masterformat 2010. A series of questions at the end of each chapter will help the reader summarize the content. The chapter on computer estimating will be expanded to cover the new estimating software for performing quantity takeoff by computer, and content covering the procedures for conceptual estimating as well as parametric estimating will be added'--
Rev. ed. of: Estimating building costs / Wayne J. DelPico. 2004.
Includes index.
Keywords: Building -- Estimates -- United States; Building -- Estimates